ANALISIS EFEKTIVITAS FLYOVER JATINGALEH BERBASIS MANAJEMEN TRANSPORTASI SEBAGAI SOLUSI KEMACETAN - Dwi Kumalasari; Tisnawati Tisnawati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2018)
Semarang is one of big city in Indonesia with a lot of activities in everyday. As the capital city of Central Java Province, Semarang City gives an active contribution which be related with the movement as human, goods and services. The movements that occurs to form knot of traffic so that give rise to traffic jam as seen on Jatingaleh Street. Because of this, it needs to be done an improvement of the capacity of a flyover and transportation management that supports it. This research aims to given flyover models based on transportation management and the policies are related in the transportation system so that is expected to overcome the traffic jam and give benefits which is in lin with the development of the city. In this research, do an analysis of Jatingaleh Street Semarang before availability the flyover and after availibility the flyover than be managed which is conformed with traffic conditions of Jatingaleh Street. Based on the calculation, after the flyover and be done manage reduction in the volume of vehicles was reduced by 4,61 % for light vehicles (LV), 2,63% for heavy vehicles (HV) and 86,59 % for motorcycle (MC) .